LA ADAPTACIÓN ECONÓMICA Y DE COMERCIALIZACIÓN DE LOS PROCESOS DE NEGOCIO EN EL MERCADO INMOBILIARIO RUSO MODERNO (Revista Inclusiones, 2018)
A model of property management in the system of business entity performance is proposed.It is based on the complexity principle, according to which the result is achieved through economic and marketing adaptation of business processes in all areas of property management.The creation of this model is driven by the existing conditions for the functioning of the economic space in Russia, the realities of business interaction in the business community, as well as the characteristics of the marketing environment that is actively developing within the framework of market relations currently forming in Russia.The content of the proposed model meets the new requirements for the processes on ensuring the real property management effectiveness at business entities,dictated by the market.These requirements in modern business are determined by the possibility of maximizing profits at the rate of exploitation of a particular propertyadmissible by the current legislation.